The literacy preparation in Turkish preschool education. - Sabri Sidekli; Semra Tican Başaran (Foxton Books, 2022)
The purpose of this study is to reveal the views and recommendations of the preschool and primary school teachers on the literacy preparation in Turkish preschool education. The study is designed as phenomenological research. The participants of the study are 12 preschool and 9 primary school teachers who have been teaching actively in the western part of Turkey. The qualitative data was collected through face-to-face interviews and analyzed through content analysis. The findings of the study show that preschool teachers have some confusion on literacy preparation and readiness. While preschool and primary school teachers are of the same opinion about the need for literacy preparation in preschool education, they have different opinions about the literacy preparation activities conducted in preschool education. While preschool teachers think that they get preschoolers ready for literacy, primary school teachers think that first graders in their classes do not come literately ready from preschool education. Teachers participated in the study; think that the lack of collaboration among preschool and primary school teachers, some deficiencies in preschool education curriculum and in the education system, and the preschool teachers' imperfect knowledge in the literacy readiness are the possible reasons of inadequacy of readiness for literacy in preschool education. They recommend systematic collaboration among teachers, review of preschool education curriculum and providing professional support for preschool teachers to support literacy readiness in preschool education.